Enhancement Effect of Berberis vulgaris var. integerrima Seeds on the Antibacterial Activity of Cephalosporins against Staphylococcus aureus and Escherichia coli: Synergistic effect of Berberis vulgaris and cephalosporins - Ahmad R. Shahverdi; Reza Moradkhani; Roholah Mirjani; Parinaz Alimirzaee; Hamid R. Monsef Esfahani; Mehrdad Iranshahi; Ahmad Reza Gohari (Iranian Journal of Pharmaceutical Sciences, 2007)
To evaluate the enhancement effect of Berberis vulgaris var. integerrima seeds on the antibacterial activity of cephalexin and ceftizoxime against Staphylococcus aureus and Escherichia coli ethanol extract of the seeds were prepared. Disk diffusion and broth dilution methods were used to determine the antibacterial activity of two cephalosporins in the absence and presence of the extract and its various fractions separated by thin layer chromatography. Clinical isolates of S. aureus and E. coli were used as test strains. Total extract and one of its fractions enhanced the antibacterial activity of cephalexin and ceftizoxime. The active component of the extract involved in the enhancement of cephalexin and ceftizoxime antimicrobial activities had an Rf of 0.47 on TLC and a lmax of 209 nm. The highest fold decrease in minimum inhibitory concentration was observed for ceftizoxime plus the active fraction of the extract against E. coli. Our preliminary results on the column chromatography and identification of the active component by high resolution mass spectroscopy showed that this minor compound may be categorized as a protoberberine structure compound. Therefore, the ethanolic extract of B. vulgaris var. integerrima seeds combined with cephalosporins may be useful against S.aureus and E. coli.